Playing along : digital games, YouTube, and virtual performance - Miller, Kiri. (Oxford ; New York : Oxford University Press, 2012)
Why don't Guitar Hero players just pick up real guitars? What happens when millions of people play the role of a young black gang member in Grand Theft Auto: San Andreas? How are YouTube-ased music lessons changing the nature of amateur musicianship? This book is about play, performance, and participatory culture in the digital age. The author shows how video games and social media are bridging virtual and visceral experience, creating dispersed communities who forge meaningful connections by "playing along" with popular culture. This book reveals how digital media are brought to bear in the transmission of embodied knowledge: how a Grand Theft Auto player uses a virtual radio to hear with her avatar's ears; how a Guitar Hero player channels the experience of a live rock performer; and how a beginning guitar student translates a two-dimensional, pre-recorded online music lesson into three-dimensional physical practice and an intimate relationship with a distant teacher. Through a series of ethnographic case studies, the author demonstrates that our everyday experiences with interactive digital media are gradually transforming our understanding of musicality, creativity, play, and participation. The book: Illuminates the actual experiences of everyday players/practitioners, instead of relying on abstract theory; Demonstrates deep connections between playing games, playing music, and playing a theatrical role; Shows how Web 2.0 platforms provide new channels for teaching and learning; Features an extensive companion website with audio and video examples.
Playing Along with Grand theft Auto: Straight outta ganton: virtual tourism, fieldwork, and performance ; Jacking the dial: radio, race, and place in San Andreas. -- Playing Along with Guitar hero and Rock Band: How musical is Guitar Hero? ; Just add performance, staging schizophonia. -- Playing Along With Communities of Practice: Music lessons 2.0 ; Amateur-to-amateur -- Endgame.
Includes bibliographical references and index.
Keywords: Video games; Video games -- Social aspects; Interactive videos; Video game music; Popular music